ASPEK PENDORONG PETANI MUDA UNTUK BERKOLABORASI DALAM KELOMPOK TANI - Gema Wibawa Mukti; Yosini Deliana; Rani Andriani Budi Kusumo (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2021)
Most young farmers in Cibodas Village, Lembang Sub-district are able to develop agriculture with modern patterns and keep up with technological developments. But, the farmer still running their agribusiness enterprises individually. The purpose of this study was to determine the characteristics of young farmers as well as the correlation with group interest and to determine the level of interest of farmers towards farmers’ group. This research is a quantitative descriptive study using an aritmaticmean and rank spearman analysis tool, the selection of samples in this study is using a purposive sampling technique of 100 samples. The results of this study show that young farmers are dominated by male farmers aged 38-44 years, at most junior high school educated and have experience of farming no more than 10 years. Access to information obtained by farmers is easy to obtain and most of them have land no more than 2.88 hectares, 78 people from 100 farmers are not affiliated with farmer groups. The level of interest of farmers is in a low category. The correlation between the characteristics of farmers and interest towards farmers’ group has a positive correlation, with indicators of education, farming experience, access to information and land area.